Extinguishing Febrile Infection-Related Epilepsy Syndrome: Pipe Dream or Reality? - Payne, Eric T.; Koh, Sookyong; Wirrell, Elaine C. (Seminars in Neurology, 2020)
Febrile infection-related epilepsy syndrome (FIRES) is a rare and devastating epileptic encephalopathy with historically abysmal neurocognitive outcomes, including a high incidence of mortality. It tends to affect children and young adults and is characterized by superrefractory status epilepticus following a recent febrile illness. Growing evidence suggests a heterogeneous etiology resulting in fulminant nonantibody-mediated neuroinflammation. For some children with FIRES, this aberrant neuroinflammation appears secondary to a functional deficiency in the endogenous interleukin-1 receptor antagonist. A precise etiology has not been identified in all FIRES patients, and current treatments are not always successful. Limited treatment evidence exists to guide choice, dosing, and duration of therapies. However, the ketogenic diet and certain targeted immunomodulatory treatments, including anakinra, appear safe and have been associated with relatively excellent clinical outcomes in some FIRES patients. Future prospective multicenter collaborative studies are needed to further delineate the FIRES heterogeneous disease pathophysiology and to determine the safety and efficacy of treatment strategies through a robust measurement of neurocognitive outcomes.
Keywords: FIRES; refractory status epilepticus; neuroinflammation